The effectiveness of A'famosa road show promotion for the year 2005 / 2006 / Amir Hussein Mohd Shariff - Mohd Shariff, Amir Hussein (Faculty of Business and Management, 2007)
The purpose of this study is to evaluate the effectiveness of road show promotion of A'Famosa Sales and Marketing Sdn. Bhd, in Kuala Lumpur. This is done by identifying several variables, which are thought able to give positive impact to sales, through surveys conducted on A'Famosa road show customers. Several analyses are carried out to evaluate the effectiveness. Methods such as frequency, crosstabulation and correlation analysis are used in this research. This study is conducted by using probability sampling with questionnaires distributed to A'Famosa road show customers; a total of 50 respondents answered the questionnaires.